8.7k views
0 votes
Is y=Tan^-1(x+pi/2) the inverse of y=Tan(x-pi/2)? Explain

User JHS
by
5.2k points

2 Answers

6 votes

Answer:

No.

Explanation:

Here we have our original function as


y=tan(x-(\pi)/(2))

in order to find its inverse , we will replace each x in above equation by y and y with x . And then we solve the new equation for y. LEt us see how :

Given


y=tan(x-(\pi)/(2))

replacing x with y and y with x


x=tan(y-(\pi)/(2))

taking tan inverse of x


tan^(-1)x=y-(\pi)/(2)

adding
\pi}{2} on both hand sides


tan^(-1)x +(\pi)/(2)=y

Hence our inverse is


y=tan^(-1)x +(\pi)/(2)

User Olf
by
5.7k points
7 votes

Answer: No, the inverse of y is y=tan(x)-pi/2


Solution

y=tan^(-1) (x+pi/2)

Solving for x:

tan(y)=x+pi/2

Subtracting pi/2 both sides of the equation:

tan(y)-pi/2 = x+pi/2-pi/2

tan(y)-pi/2 = x

x=tan(y)-pi/2

Changing x by y and y by x:

y=tan(x)-pi/2

User Georgy Gobozov
by
6.5k points